2020
DOI: 10.1017/s0022215119002573
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of successful tracheostomy decannulation in children: a multicentric cohort study

Abstract: BackgroundDetermining prognostic factors for the probability of tracheostomy decannulation is key to an adequate therapeutic plan.MethodsA retrospective cohort study of 160 paediatric patients undergoing tracheostomy was conducted. Associations between different parameters and eventual tracheostomy decannulation were assessed.ResultsMean follow-up duration was 27.8 months (interquartile range = 25.5–30.2 months). Median age at tracheostomy was 6.96 months (interquartile range = 3.37–29.42 months), with median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…As reported in previous studies, the most common underlying comorbidity in children with tracheostomy were neurologic disorders in our study 19,20 . Fourteen of 22 children had a neurologic illnes, and additonal four children had a concomittan neurologic impairment such as hypotonia.…”
Section: Discussionsupporting
confidence: 84%
“…As reported in previous studies, the most common underlying comorbidity in children with tracheostomy were neurologic disorders in our study 19,20 . Fourteen of 22 children had a neurologic illnes, and additonal four children had a concomittan neurologic impairment such as hypotonia.…”
Section: Discussionsupporting
confidence: 84%
“… Note : Schweiger et al 15 , Maslan et al 19 , Prickett et al 26 , and Al‐Saati et al 8 were excluded from this analysis as the primary indication for tracheostomy was not clearly described. …”
Section: Resultsmentioning
confidence: 99%
“…However, only three protocols monitored children for the 24-48-h period suggested by the ATS. 6,15,16 Some authors suggest that shorter observation periods are safe and promote resource conservation. For example, Prickett and Sobol 26 found that all decannulation failures in their study occurred within the first 12 h. Observation typically occurred on the inpatient ward or ICU setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations